(3eTcd GdbQBfs - (3YHO Gddg Hf eSde Hf bJjHI GdOjnfnhQqj, CHh eMeO, GHf obnJrjnHI, J (B276 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi fgL dfG SHd GdQTGO s
(3BNQgG (B:s
(3jfJgi GKfGA HGH GddMf Hbhdg hCeQge Cf jbWYhG cd eUMa hLOhg eNGdakG deUMa YKeGf QMeg Gddg CNHQfi HPdc CHh MGJe Yf GdCUeYi s
(3cJHJ Ydi Qb ZRGds
(3bWYI efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B137s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJaSjQ hYdhe GdbQBfs